Rancang Bangun Sistem Informasi Penerimaan Siswa Baru Sekolah Dasar YPK Yoka Baru Waena - Kean, Desman; Irjanto, Norman S. (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2024)
The procedure for adding new students at SD YPK Yoka Baru has obstacles related to the accumulation of files and lack of transparency. To address this, a new online system for students was created with the aim of increasing efficiency and transparency. The system was created using the Waterfall model, which involves requirements analysis, planning, coding and testing. The test method using black boxes ensures that every component of the system is effective and that input validation protocols are followed as appropriate. The test results show the effectiveness of the system in displaying accurate error messages when the input is incorrect, as well as making it easier to verify data. The implementation of this system reduces the chances of file corruption or loss, speeds up the administrative process, and improves the experience of prospective students and their parents. As a result, this system can be a prototype for other educational institutions that utilize the web in their admissions process.Keywords: Information systems; New student admissions; Web-based; Efficiency, transparency.Â AbstrakProsedur penambahan siswa baru di SD YPK Yoka Baru memiliki kendala terkait penumpukan berkas dan kurang transparan. Untuk mengatasi hal ini, sistem online baru untuk siswa diciptakan dengan tujuan meningkatkan efisiensi dan transparansi. Sistem ini dibuat menggunakan model Waterfall, yang melibatkan analisis persyaratan, perancangan, pengkodean dan pengujian. Metode pengujian menggunakan black box memastikan bahwa setiap komponen sistem efektif dan protokol validasi input diikuti sebagaimana mestinya. Hasil pengujian menunjukkan efektivitas sistem dalam menampilkan pesan kesalahan yang akurat ketika input salah, serta memudahkan verifikasi data. Penerapan sistem ini mengurangi kemungkinan kerusakan atau kehilangan file, mempercepat proses administrasi, dan meningkatkan pengalaman calon siswa dan orang tuanya. Hasilnya, sistem ini dapat menjadi prototipe bagi institusi pendidikan lain yang memanfaatkan web dalam proses penerimaannya.Â